Potent Natural Antioxidant Carveol Attenuates MCAO-Stress Induced Oxidative, Neurodegeneration by Regulating the Nrf-2 Pathway - Malik, Imran; Shah, Fawad Ali; Ali, Tahir; Tan, Zhen; Alattar, Abdullah; Ullah, Najeeb; Khan, Arif-ullah; Alshaman, Reem; Li, Shupeng (Frontiers in Neuroscience, 2020)
Ischemic stroke is a severe neurological disorder with a high prevalence rate in developed countries. It is characterized by permanent or transient cerebral ischemia and it activates syndrome of pathological events such as membrane depolarization, glutamate excitotoxicity, and intracellular calcium buildup. Carveol is widely employed as anti-inflammatory and antioxidant in traditional Chinese medicine. In the present study, the neuroprotective effects of post-treated carveol were demonstrated against transient middle cerebral artery occlusion (MCAO) induced focal ischemic cerebral injury. Male SD rats were subjected to two different experimental protocols to determine the dose and effects of carveol, and to demonstrate the underlying role of the nuclear factor E2-related factor (Nrf2) pathway. Our results showed that MCAO induced marked neuronal injury in the ipsilateral cortex and striatum associated with higher inflammatory cytokines expression, along with apoptotic markers such as caspase-3 and p-JNK. Furthermore, MCAO induced a marked increase in oxidative stress as evidenced by high lipid peroxidase (LPO) content accompanied by the depressed antioxidant system. Carveol significantly reversed the oxidative stress in a dose-dependent manner and downregulated inflammatory cascades by enhancing endogenous antioxidant mechanisms including the Nrf2 gene, which critically regulates expression of several downstream antioxidants. Further, to determine the possible involvement of Nrf2 in carveol mediated neuroprotection, we antagonized Nrf2 by all-trans retinoic acid (ATRA), and such treatment abrogated the protective effects of carveol accompanied with exaggerated neuronal toxicity as demonstrated by higher infarction area. The target effects of carveol were further supported by molecular docking analysis of drug-protein interactions. Together, our findings suggest that carveol could activate Nrf2, which further regulates the expression of downstream antioxidants, eventually ameliorating MCAO-induced neuroinflammation.